The Propagation Velocity of Decca-Frequency Transmissions over Sea Ice - Gray, David H. (The International Hydrographic Review, 2015)
In April and August 1973, a phase lag comparison test was performed using a double monitor system with the hyperbolic Decca chain established for various scientific surveys in the Amundsen Gulf. The test compared the secondary phase lag effect of sea ice and sea water. The observed values of the August test over sea wafer are consistent with the theoretical formulas of J.R. Johler. The observed values of the April test over sea ice cannot be compared with the formulas because the formulas are based on the assumption of a vertically homogeneous medium and this assumption is not valid in a sea-ice situation. The observed average velocity over sea ice is 299 510 km/sec and over sea water is 299 610 km/sec.